Public-private partnerships in the water sector: A review - Lima, S.; Brochado, A.; Marques, R. C. (Utilities Policy, 2021)
Public-private partnerships (PPPs) offer possible solutions for governments seeking to achieve better value for money and fund the investments needed to provide infrastructure and manage public services. Water-sector projects demand extensive, up-front and sunk investments, and inefficiency levels are often significant. This study conducted a systematic review of previous research on water sector PPP projects. The research design is innovative in that it relied on a hybrid methodology combining systematic quantitative, semantic network and narrative analyses. The literature review protocol applied found 122 relevant studies published in top journals. Five key topics within water-related PPP studies were identified: risk management, PPP contractual arrangements, financing and tariffs, infrastructure, and governance. The most important topic is risk management, within which individual scholars’ contributions were tracked. However, a consensus has not been reached about the best risk matrix for improving PPP contracts in the water sector.